2001
DOI: 10.1023/a:1012074606561
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: One hundred landraces of maize from Northern Spain were characterized on the basis of twenty-two morphological traits, and seventeen ecological variables (climatic, edaphic and topographic) associated with the collection site. High broad-sense heritabilities (>0.6) were found for plant height, ear height, ear node number, ear length, mid-ear diameter, rows of kernels, kernels per row, cob weight and days to silking. Seven different groups were obtained with cluster analysis using plant and cycle traits, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Many tools are now available to study relationships among cultivars, including various types of molecular markers; however, morphological characterization is the first step in the description and classification of germplasm (Smith and Smith, 1989). Ruiz de Galarreta and Alvarez (2001) in a study of one hundred landraces of maize from Northern Spain on the basis of twenty-two morphological traits, and seventeen ecological variables associated with the collection site, the study reported that seven different groups were obtained from the cluster analysis using plant and cycle traits. Seven populations with promising breeding values were detected.…”
Section: Introductionmentioning
confidence: 99%
“…Many tools are now available to study relationships among cultivars, including various types of molecular markers; however, morphological characterization is the first step in the description and classification of germplasm (Smith and Smith, 1989). Ruiz de Galarreta and Alvarez (2001) in a study of one hundred landraces of maize from Northern Spain on the basis of twenty-two morphological traits, and seventeen ecological variables associated with the collection site, the study reported that seven different groups were obtained from the cluster analysis using plant and cycle traits. Seven populations with promising breeding values were detected.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the genetic diversity of ex situ conserved European maize landraces has been extensively studied using genetic (Dubreuil and Charcosset 1999;Rebourg et al 1999Rebourg et al , 2003Rebourg et al , 2001Gauthier et al 2002;Gouesnard et al 2005;Reif et al 2005b;Camus-Kulandaivelu et al 2006;Dubreuil et al 2006) and morphologic descriptors (Brandolini and Brandolini 2001;de Galarreta and Alvarez 2001). Landraces from Switzerland and adjacent regions of Austria, however, were under-represented in the European maize collections (cf., Gauthier et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cob length is related to number of grains per cob and the factors reducing number of grains per cob also reduced cob length. Cob length is an important yield factor that is positively related to grain yield and has high heritability (Ruiz de Galarreta and Alvarez, 2001;Lucchin et al, 2003). Additionally, cob length is also affected by genetic structure, environmental factors, cultivation techniques such as planting time, plant density and nitrogen dose.…”
Section: Grain Yield and Yield Components Of Cornmentioning
confidence: 99%